Treatment outcome and follow-up pattern of breast cancer patients with locally advanced and/or metastatic disease receiving intravenous chemotherapy during COVID-19 Pandemic: A descriptive correlational study - Paulo Martin B. Villanueva; Judy Ann B. Surtida; May Sabando (Northern Negros State College of Science and Technology (NONESCOST), 2022)
The study determined the impact COVID-19 pandemic on treatment outcomes and follow-up patterns of breast cancer patients at Bicol Cancer Center of Bicol Regional Training and Teaching Hospital (BRTTH). The study utilized a retrospective and descriptive study. Of the 108 breast cancer patients, 73 or 67.59 percent had followed up as scheduled during the pandemic; while there was 35 or 32.41 percent who had delayed follow-up. Of the total number of subjects with treatment delays, there were 7 or 6.48 percent with the stable disease while 24 or 22.22 percent were already found with progressive disease. For breast cancer patients with no treatment delays, there was 71 or 65.74 percent with stable disease and 6 or 5.56 percent were found to have a progressive disease. A chi-square test of independence was performed to examine the comparison of outcomes between those with treatment delay and those with no treatment delay. The relation between these variables was significant, X2 (1, N = 108) = 49.9951, p = <0.00001. Patients with no treatment delays were more likely to have a stable disease compared to those with treatment delays. There is a high percentage of follow-ups as scheduled despite the COVID-19 pandemic. The incidence of progressive disease is higher among patients who received treatment delay as compared to those who did not have treatment delay. Patients with breast cancer who do not follow up as scheduled which causes treatment delays are at higher risk of having more severe or progressive disease.